2016
DOI: 10.1002/eqe.2794
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of earthquake damaged external RC beam‐column joints by joint enlargement using prestressed steel angles

Abstract: Summary The effectiveness of a rehabilitation method based on joint enlargement using prestressed steel angles to enhance the seismic behavior of damaged external reinforced concrete beam‐column joints was experimentally investigated. Three half‐scale joints having either non‐seismic or seismic reinforcement details were tested both before and after rehabilitation by applying lateral cyclic loading of increasing amplitudes. Two defects were considered for the two non‐seismic units, being the absence of transve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…In the scope of the study, a total of 12 test specimens were produced and loaded up to the gravity at the axial concentric loading effect. The results obtained show that the repair detail of the used hybrid CFRP strips and carbide rods gives successful results for repairing the columns [34]. In addition to the CFRP reports, TRM reinforced concrete columns have been reinforced in recent years for the reasons explained above.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the scope of the study, a total of 12 test specimens were produced and loaded up to the gravity at the axial concentric loading effect. The results obtained show that the repair detail of the used hybrid CFRP strips and carbide rods gives successful results for repairing the columns [34]. In addition to the CFRP reports, TRM reinforced concrete columns have been reinforced in recent years for the reasons explained above.…”
Section: Introductionmentioning
confidence: 83%
“…Although positive results were obtained in terms of bearing power, the difficulties caused a decrease in the use of the sheathing, such as the difficulties experienced in the formwork, reinforcement and concrete works, the inability to use the framework when reinforcing the building, deteriorating the building's architecture, etc. Instead, reinforcing structural elements against shear and bending forces with steel elements came into prominence [7][8][9]. Risks, costs, and architectural issues caused by adverse environmental impacts, unqualified workmanship, fire, or corrosion were met in this reinforcement process.…”
Section: Introductionmentioning
confidence: 99%
“…Priestley [13][14][15] studied the seismic performance of precast concrete frame buildings, beam-column joints, and shear walls and put forward several design suggestions. Shafaei et al [16,17] studied the seismic performance of beam-column joints having either nonseismic or seismic reinforcement details, and the results indicated that rehabilitated methods can recover the mechanical properties. Elsanadedy [18] attempted to develop new precast moment connections for increasing the progressive collapse robustness of precast buildings.…”
Section: Introductionmentioning
confidence: 99%
“…They are verified through experiments and numerical calculations that these seismic strengthening strategies are very effective in improving the seismic performance of structures. Other researchers focus on the use of different types of buckling‐restrained braces, 13–15 RC and steel jackets, 16–18 ferrocement jackets, 19–21 steel and aluminum shear panels, 22–24 steel prop and curb, 25,26 diagonal haunch, 27,28 shape memory alloy, 29–31 prestressed steel angles, 32–34 isolation devices, 35 and metal plate shear walls 36 for the upgrade and modification of RC frame structures. And they are also verified by experiments and numerical calculations that these seismic upgrading strategies are very effective in improving the seismic performance of structures.…”
Section: Introductionmentioning
confidence: 99%